Molecular simulation of (Al–Ga) surface garnished with chromium metal for organic material detecting: A DFT study - Mollaamin, Fatemeh; Monajjemi, Majid (World Scientific Pub Co Pte Ltd, 2023)
Al–Ga surface doped with chromium (Cr) is theoretically studied using first-principles density functional theory (DFT) at the CAM-B3LYP/EPR-III, LANL2DZ, 6-31+G(d,p) level of theory to explore the chemical adsorption and corrosion inhibition of organic carbenes through coating process. Crystal structure of Cr–(Al–Ga) surface was coated by S–&N–heterocyclic carbenes of benzotriazole (BTA), 2-mercaptobenzothiazole (2MBT), 8-hydroxyquinoline (8HQ) and 3-amino-1,2,4-triazole-5-thiol (ATR). The NMR spectroscopy of the adsorption of BTA, 2MBT, 8HQ, and ATR on the Cr-doped Al–Ga nanoalloy surface represents that this surface can be employed as the magnetic S–&N–heterocyclic carbene sensors. In fact, Cr site in Cr–(Al–Ga) nanoalloy surface has bigger interaction energy amount from Van der Waals’ forces with BTA, 2MBT, 8HQ, and ATR that might cause them large stable towards coating data on the nanosurface. It has been estimated that the criterion for choosing the surface linkage of S and N atoms in BTA, 2MBT, 8HQ, and ATR in adsorption sites can be impacted by the existence of close atoms of aluminum and gallium in the Cr–(Al–Ga) surface. The fluctuation of NQR has estimated the inhibiting role of BTA, 2MBT, 8HQ, and ATR for Cr -doped Al–Ga alloy nanosheet due to S and N atoms in the benzene cycle of heterocyclic carbenes being near the monolayer surface of ternary Cr–(Al–Ga) nanoalloy. Moreover, IR spectroscopy has exhibited that Cr-doped Al–Ga alloy nanosheet with the fluctuation in the frequency of intra-atomic interaction leads us to the most considerable influence in the vicinage elements generated due to inter-atomic interaction. Comparison to [Formula: see text]G[Formula: see text]˙adsamounts versus dipole moment has illustrated a proper accord among measured parameters based on the rightness of the chosen isotherm for the adsorption steps of the formation of BTA @ Cr–(Al–Ga), 2MBT @ Cr–(Al–Ga), 8HQ @ Cr–(Al–Ga), and ATR @ Cr–(Al–Ga) complexes. Thus, the interval between sulfur, nitrogen, and oxygen atoms in BTA, 2MBT, 8HQ, and ATR during interaction with transition metal of Cr in Cr–(Al–Ga) nanoalloy, (N[Formula: see text]Cr, O[Formula: see text]Cr, S[Formula: see text]Cr), has been estimated with relation coefficient of [Formula: see text]ˆ2 = 0.9509. Thus, this paper exhibits the influence of Cr doped on the “Al–Ga” surface for adsorption of S–&N–heterocyclic carbenes of BTA, 2MBT, 8HQ, and ATR by using theoretical methods. Furthermore, the partial electron density or PDOS has estimated a certain charge assembly between Cr–(Al–Ga) and S–&N–heterocycles of BTA, 2MBT, 8HQ, and ATR which can remark that the complex dominant of metallic features and an exact degree of covalent traits can describe the augmenting of the sensitivity of Cr–(Al–Ga) surface as a potent sensor for adsorption of BTA, 2MBT, 8HQ, and ATR heterocycles. This work investigates the characteristics, band structure, and projected density of state (PDOS) of Al–Ga nanoalloy doped with Cr element for increasing the corrosion inhibition of the surface through adsorption of organic molecules of carbenes in the surface coatings process. This paper can be helpful in a range of applications which uses Al–Ga alloy for the study of energy storage and adsorption of air pollution or water contamination. Many different approaches such as surface coatings, alloying, and doping can be adopted to protect the surface.
Keywords: 13. Climate action